KEPADATAN POPULASI MAMALIA DARAT KARNIVORA DI CAMP LEAKEY KAWASAN TAMAN NASIONAL TANJUNG PUTING, KALIMANTAN TENGAH: Population Density Of Terrestrial Mammalian Carnivore In Camp Leakey, Tanjung Puting National Park, Central Borneo - Mandiri, Siwi Arthapati; Sukandar, Paskal; Istiadi, Yossa (Bioma, 2016)
Borneo has wide land that support high biodiversity. One of them is Tanjung Puting National Park (TPNP), which have biodiversity such as terrestrial mammalian carnivore. Carnivore has a role to maintain its ecosystems. But, there are no data for population density of terrestrial mammalian carnivore. The object of this research is to find out population density of terrestrial mammalian carnivore in Camp Leakey, TPNP, Central Borneo. This research accomplished in September-October 2015 in Camp Leakey. Using line-transect sampling. Data collection was accomplished at 18.00-24.00 Central Indonesian Time (WITA) on eight transects with three times replication by direct surveys and indirect surveys. This research has obtained five species, malayan sun bear (Helarctos malayanus), sunda clouded leopard (Neofelis diardi), leopard cat, and group of civet, like small-toothed palm civet (Arctogalidia trivirgata) and asian palm civet (Paradoxurus hermaphroditus). Population density of each species from the highest to the lowest is 13,5 Individual of leopard cat/km2, 9,84 Individual of malayan sun bears/km2, 4,31 Individual of sunda clouded leopard/km2, and 3,65 Individual of civet/km2. Malayan sun bears, sunda clouded leopards and civets prefer to be in land forest. Leopard cats prefers to be in transition forest.